Artisanal fishers’ local ecological knowledge and attitudes toward conservation about the shrimp (Xiphopenaeus kroyeri) on the Brazilian central coast - MUSIELLO-FERNANDES,JOELSON (2021)
Abstract In order to contribute to the management of small-scale trawling fishing of the Xiphopenaeus kroyeri shrimp, the aim of this study was to evaluate the local ecological knowledge (LEK) and the conservationist attitudes of artisanal fishers in four fishing communities along the central Brazilian coast. This study was based on 80 ethnographic interviews conducted in two communities are in the state of Bahia (Santa Cruz Cabrália and Barra de Caravelas) and two communities in the state of Espírito Santo (Barra Nova and Anchieta). The fishers present knowledge compliance with literature, except in aspects reproductive of the shrimp and are willing to exchange knowledge with researchers. The mean attitude index of the fishers was 0.65. Education activities should focus on the reproductive biology of shrimp to include fishing communities in the drafting of legislation about closed season period, as this issue is directly related to possible divergences between fishers do not adhere to them. The results suggest that, dialogue and knowledge exchange is necessary among the stakeholders, including the fishers, scientists and managers, who are responsible for the elaboration of management measures.